Pediatric Nurses' Knowledge of and Self-Efficacy in Breastfeeding Counseling - Farrag, Nesrine Saad; Abdelsalam, Sherehan Adel; Laimon, Wafaa; El-Gilany, Abdel-Hady (American Journal of Perinatology, 2019)
Objective Sound breastfeeding (BF) knowledge among health professionals is vital for proper institutional support of BF mothers. This study aims to measure both BF knowledge and self-efficacy (SE) of pediatric nurses in supporting BF and to determine their associated factors.Study Design A cross-sectional study was conducted in Mansoura University Children's Hospital and Mansoura New General Hospital during the period from January to March 2017. A total of 186 nurses completed a predesigned self-administered questionnaire developed by the investigators to measure BF knowledge and SE in BF counseling.Results The overall total means of BF knowledge and SE scores were 26.8 (6.4) and 3.8 (0.6), respectively. Linear regression showed that having bachelor education, working in neonatal department, having a child (aged 2–5 years) were significant independent predictors of BF knowledge score (R2 = 0.448, p ≤ 0.001), while BF knowledge score is the only significant independent predictor of SE in BF counseling (R2= 0.36, p ≤ 0.001).Conclusion Higher pregraduation education, working in neonatal department, having children aged 2 to 5 years are independent predictors of BF knowledge. Improving BF knowledge may improve nurses' SE in supporting BF.
Keywords: breastfeeding; breastfeeding knowledge; breastfeeding support; counseling; nurses; self-efficacy